2020
DOI: 10.1016/j.orcp.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Body composition influences blood pressure during submaximal graded test in women

Abstract: Article type Original research Running head Exercise blood pressure in women Abstract word count 211 w Text-only word count 2762 w Number of tables and figures 3 figures, 1 table Number of references 27 Competing interests None Funding received

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…It is postulated that high sympathetic nervous system activity and activation of the renin-angiotensin-aldosterone system result in sodium and water retention and higher baseline SBP and DBP in obese individuals. [ 17 ] Similar findings were reported by Kerhervé et al ,[ 18 ] who observed that obese individuals had higher SBP, DBP, and MAP in comparison to normal weight ( P = 0.015, P = 0.004, and P = 0.004) and overweight individuals ( P = 0.002, P < 0.001 and P < 0.001) at rest and during exercise due to obesity-specific sympathetic nervous system activity dysregulation. Gowdhami et al .…”
Section: Discussionsupporting
confidence: 83%
“…It is postulated that high sympathetic nervous system activity and activation of the renin-angiotensin-aldosterone system result in sodium and water retention and higher baseline SBP and DBP in obese individuals. [ 17 ] Similar findings were reported by Kerhervé et al ,[ 18 ] who observed that obese individuals had higher SBP, DBP, and MAP in comparison to normal weight ( P = 0.015, P = 0.004, and P = 0.004) and overweight individuals ( P = 0.002, P < 0.001 and P < 0.001) at rest and during exercise due to obesity-specific sympathetic nervous system activity dysregulation. Gowdhami et al .…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, there is currently little consensus regarding the optimal training intensity specifically in women, despite the specific challenges pregnancy, menopause and contraception impose on cardiovascular health [29]. Despite normal heart rate responses during graded exercise performed at 30-60% of _ VO 2MAX , significantly different blood pressure responses have been reported in obese compared to normal and overweight women [30]. Fat oxidation of independent groups of obese/overweight women has been reported to be lower [31], similar [32][33][34][35] or even greater [36] than lean women during constant work rate cycling at discrete exercise intensities from 50% to 65% of _ VO 2MAX .…”
Section: Introductionmentioning
confidence: 99%